If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2Y + -6 = -34 Reorder the terms: -6 + 2Y = -34 Solving -6 + 2Y = -34 Solving for variable 'Y'. Move all terms containing Y to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 2Y = -34 + 6 Combine like terms: -6 + 6 = 0 0 + 2Y = -34 + 6 2Y = -34 + 6 Combine like terms: -34 + 6 = -28 2Y = -28 Divide each side by '2'. Y = -14 Simplifying Y = -14
| z-3/5=4 | | (2*x/3*y)^5 | | y=98-2x^2 | | 2x^2-2x^2-12x= | | (4x-3)(5x+2)=0 | | 15x^3y^4-60xz^8=0 | | z-5/3=4 | | 81=y^2+2y^2 | | 3/5-z=4 | | x^2+4x+4=6+3x | | I/9-4=-23 | | 3/5-5/3=4 | | 3x^3-5x^2=6 | | 3a-2+5a-7= | | 3/5-5/3 | | ((3-(3/2x))^2) | | x-3/5=4 | | 5+(4m-9)= | | 124=y+3x^3 | | (3-(3/2x))^2 | | -3y-17=27-7 | | 5/3-z=4 | | x=8+-3y | | 2.5x+5y=35 | | W/-11+8=5 | | 1/3q=-7 | | 5/4x-7x=6 | | 5a-7a+2= | | 20-5(p-1)+3p=(2p-15) | | (3-3/2x)^2 | | 12-3z+2y-4x=0 | | 6x-2+7x= |